Group Investigation Model (Pengembangan Model Pembelajaran Untuk Meningkatkan Kemampuan Profesional Mahasiswa Sebagai Calon Guru) - Aunurrahman, - (Jurnal Pembelajaran Prospektif, 2016)
This research was directed to find out â€œpenerpanâ€ model of investigative group in the learning process to support the preparation of candidates for professional teachers in the Faculty of Education in University of Tanjungpura. The approach used in this study is a combination of qualitative and quantitative approaches (mixing qualitative and quantitative method), which was developed through the course of Professional Education on research subjects of Physics Education Study Program students who take these courses. The study found that the group investigating models were able to improve their knowledge and understanding about the implementation of the learning process in schools. Similarly, this model was able to increase the the studentsâ€™ dimensions of values applied to improve the ability of students. This is the model of investigative group designed and implemented in an integrated manner for the subject courses of Professional Education, by optimizing the active role of students as well as institutional support. This study recommends that this model was developed for a wider variety of courses for improving the knowledge and the expansion of the studentsâ€™ experience. In addition, the need for further research deepens or extends the findings of this study.